Simulation and Experiment of the Homogeneously Catalyzed Production of Terpenyl Amine. Issue 7 (8th May 2018) - Schulz, Robin; Sengen, Laura; Gießelmann, Katja; Hunold, Sira; Zeiner, Tim
Abstract: Continuous terpenyl amine production via a homogeneously catalyzed hydroamination is presented. For the recycling of the catalyst a liquid‐liquid system combined with a subsequent acid complexation as capturing step for the terpenyl amine was used. The whole process was run in pilot plant scale. At first, batch experiments were conducted to determine reaction equilibria of the hydroamination and the acid complexation. On this, a process model was developed which is based on equilibrium stages. This process model was validated by running the continuous process and was able to predict the continuous process in good agreement with experimental data. So, it allows a reduction of the experimental effort. Abstract : A continuous production of terpenyl amine by reactive extraction was investigated. Experiments were done in laboratory scale and continuously in a pilot plant. A process model based on laboratory tests has been developed and validated. On this basis, this model reduces the experimental effort for further reactive extractions.